Modelos e taxas de atração de viagens para PGVs - Hospitais públicos localizados em cidades de médio porte do interior do estado de São Paulo - Gontijo, Geisa Aparecida da Silva (Universidade Federal de São Carlos, 2012)
This work aims to present trip attraction models and rates to public hospitals located in mediumsized cities in the interior of the state of São Paulo Brazil. The hospitals cause significant impacts in the local traffic and because of that they can be characterized as Potential Trip Generation Centers. In this sense, this research presents rates and models that allow us to analyze the possible impacts related to trips attracted by new hospitals. In the development of the proposed models and rates, it was performed a research in seven Santas Casas de Misericórdia hospitals in seven medium-sized cities: São Carlos, Marília, Sertãozinho, Rio Claro, Jaú, Mogi- Guaçú and Araras. The data of the first five cases were used in the development of the trip attraction models and rates, while the last two ones were used to validate the developed models. In these hospitals were performed traffic counting of pedestrians, private vehicles, buses, motorcycles and bicycles, and also interviews with the users. Through the developed analysis were elaborated models of simple regression, multiple regressions, simple regression by trip objective and mode of transport and multiple regressions with dummy variables. Some of the models developed were validated by data collected and thus they were considered more reliable to be used in Brazilian hospitals than models of the Institute of Transportation Engineers-ITE. To complement this study, it was performed a doctoral internship in Madrid, Spain in 2011 where specific models were developed with data from four public hospitals of that city. Through the application of the elaborate models and the models of ITE, it was found that the models developed for Madrid are also more suitable to estimate the travels to Spanish hospitals than the models of the ITE. Thus, this study found that for Brazilian cities, where the second mode of transportation is the bus, and for the Spanish city where the second mode of transportation is the subway, the ITE models, that consider only travels by car, may not be sufficient to estimate the travels.
Keywords: Planejamento urbano; Pólos geradores de viagens; Hospitais públicos; Modelos de geração de viagens; Potential trip generation centers; Public hospitals; Trip attraction models; ENGENHARIAS